The Power of Place in Citizen Science - McGreavy, Bridie; Newman, Greg; Chandler, Mark; Clyde, Malin; Haklay, Muki; Ballard, Heidi; Gray, Steven; Scarpino, Russel; Hauptfeld, Rita; Gallo, John (Maine Policy Review, 2017)
These authors answer the question: What are the links between motivations for citizen science, connections to place, and conservation decision outcomes?